Linking pattern recognition and salicylic acid responses in Arabidopsis through ACCELERATED CELL DEATH6 and receptors - Tateda, Chika (Plant Signal Behav, 2015)
The Arabidopsis membrane protein ACCELERATED CELL DEATH 6 (ACD6) and the defense signal salicylic acid (SA) are part of a positive feedback loop that regulates the levels of at least 2 pathogen-associated molecular patterns (PAMP) receptors, including FLAGELLIN SENSING 2 (FLS2) and CHITIN ELICITOR RECEPTOR (LYSM domain receptor-like kinase 1, CERK1). ACD6- and SA-mediated regulation of these receptors results in potentiation of responses to FLS2 and CERK1 ligands (e.g. flg22 and chitin, respectively). ACD6, FLS2 and CERK1 are also important for callose induction in response to an SA agonist even in the absence of PAMPs. Here, we report that another receptor, EF-Tu RECEPTOR (EFR) is also part of the ACD6/SA signaling network, similar to FLS2 and CERK1.